The Influence of Motivation, Work Discipline and Leadership on Employee Performance: Pengaruh Motivasi, Disiplin Kerja dan Kepemimpinan Terhadap Kinerja Karyawan - Sudibyo, Eko; Sukmono, Rita Ambarwati (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to analyze and prove the effect of motivation, work discipline and leadership on the performance of employees of PT. Djabes Tunas Utama Mojokerto. The study was conducted with a quantitative approach, with sampling using probability sampling technique totaling 142 employees. The analysis technique used is multiple linear regression. Based on the results of research data analysis, the results obtained either partially or simultaneously motivation, work discipline and leadership proved to have a significant contribution to the performance of employees of PT. Djabes Tunas Utama Mojokerto. Other results show that motivation, work discipline and leadership have a contribution of 82.5% to employee performance.